The Energy-Coupling Factor Transporter Module EcfAA’T, a Novel Candidate for the Genetic Basis of Fatty Acid-Auxotrophic Small-Colony Variants of Staphylococcus aureus - Schleimer, Nina; Kaspar, Ursula; Drescher, Mike; Seggewiß, Jochen; von Eiff, Christof; Proctor, Richard A.; Peters, Georg; Kriegeskorte, André; Becker, Karsten (Frontiers in Microbiology, 2018)
Staphylococcal small-colony variants (SCVs) are invasive and persistent due to their ability to thrive intracellularly and to evade the host immune response. Thus, the course of infections due to this phenotype is often chronic, relapsing, and therapy-refractory. In order to improve treatment of patients suffering from SCV-associated infections, it is of major interest to understand triggers for the development of this phenotype, in particular for strains naturally occurring in clinical settings. Within this study, we comprehensively characterized two different Staphylococcus aureus triplets each consisting of isogenic strains comprising (i) clinically derived SCV phenotypes with auxotrophy for unsaturated fatty acids, (ii) the corresponding wild-types (WTs), and (iii) spontaneous in vitro revertants displaying the normal phenotype (REVs). Comparison of whole genomes revealed that clinical SCV isolates were closely related to their corresponding WTs and REVs showing only 7-8 alterations per genome triplet. However, both SCVs carried a mutation within the energy-coupling factor (ECF) transporter-encoding ecf module (EcfAA’T) resulting in truncated genes. In both cases, these mutations were shown to be naturally restored in the respective REVs. Since ECF transporters are supposed to be essential for optimal bacterial growth, their dysfunction might constitute another mechanism for the formation of naturally occurring SCVs. Another three triplets analyzed revealed neither mutations in the EcfAA’T nor in other FASII related genes underlining the high diversity of mechanisms leading to the fatty acid-dependent phenotype. This is the first report on the ECF transporter as genetic basis of fatty acid-auxotrophic staphylococcal SCVs.